Characterization of type IIX muscle fibres in the mouse. - Zampini, Daniela Zardini. (University of Ottawa (Canada), 1993)
The properties of type IIX fibres in mouse skeletal muscle and the factors affecting the expression of myosin heavy chain (MHC) in these fibres were studied. Type IIX fibres were recognized on the basis of a lack of staining with antibodies directed against type I, IIA and IIB MHC. The IIX MHC isoform contained a determinant common to all type II MHCs, but lacked epitopes specific for types IIA and IIB MHCs, as well as an epitope that was present in all other MHCs. Fibres expressing IIX MHC accounted for about one-third of the total fibre number in mouse fast-twitch muscles. Sciatic nerve crush with subsequent reinnervation resulted in the formation of "type IIX fibre groups" in tibialis anterior and gastrocnemius, suggesting that the IIX phenotype is neurally regulated. The association of specific MHC isoforms with individual fibre types was confirmed by gel electrophoresis. Using 5%, 6% and 3-5% gradient sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) IIX MHC was found to co-migrate with IIA MHC. Immunohistochemistry and gel electrophoresis of single fibres from the superficial part of the tibialis anterior muscle (TAS) showed the existence of hybrid fibres co-expressing IIB and IIX MHC. Myosin light chain (MLC) analysis of IIX fibres revealed the presence in these fibres of MLC 3f in amounts significantly smaller than that contained in IIB fibre types which suggests that type IIX fibres have a lower Vo than type IIB fibres. Physiological, histochemical and morphometrical properties of fast-twitch single motor units were studied. Single motor units were functionally isolated by microdissection of the ventral root, the glycogen depletion technique was used to demonstrate the muscle fibres in the motor unit and monoclonal antibodies were used to identify their MHC composition in order to correlate physiological, histochemical and morphometrical studies. These studies revealed that IIX motor units had contractile properties similar to those of types IIA and IIB motor units but had morphological, physiological and biochemical properties that distinguish them from the latter two types. IIX motor units had a resistance to fatigue, cross-sectional fibre area and motor unit area intermediate between IIA and IIB motor units. Finally, the effect of altered thyroid hormone status and age on the expression of IIX MHC was studied. Hypothyroidism led to a decrease in the expression of IIB MHC and an increase of IIX MHC in TAS muscle, while hyperthyroidism had no significant effect. The proportion of type IIX and IIB fibres in TAS muscle of the mouse undergoes specific age-related changes that can not be detected with conventional histochemical techniques. Specifically, the proportion of fibres expressing IIB MHC decreased and the proportion of fibres expressing type IIX and co-expressing type IIB and IIX MHC increased with age. It is proposed that fibres co-expressing IIX and IIB MHC represent a transitional fibre type involved in an age-related transformation process.
Keywords: Biology, Animal Physiology.